DISENFRANCHISEMENT OF CORRUPT POLITICS IN INDONESIA IN THE PERSPECTIVE OF SIYASAH SYAR’IYYAH - Muhammad Fitrah; Djafar, Usman (SIYASATUNA : JURNAL ILMIAH MAHASISWA SIYASAH SYAR’IYYAH, 2025)
The revocation of political rights is basically an addition to the punishment of corruptors. With that decision, convicts lose their right to vote and be elected apart from holding public office. The research used is library research (library reasearch). The approach used is normative juridical, which examines the application of rules or norms in Indonesian law, and syar’i theology, namely studying it from the perspective of Islamic law. The data sources used are primary data sources in the form of Laws, Criminal Code, Al-Qur’an and Hadith and secondary data in the form of books related to research and research journals. The results of this study indicate that the rules used for the revocation of political rights against corruptors in Indonesia are based on PKPU No. 20 of 2018 Article 7 Paragraph (1) Point (h), namely that prospective candidates for members of the DPR, Provincial DPRD and Regency/City DPRD are not former convicts of drug dealers, sexual crimes against children, or corruption. Keywords: Repeal, Political Rights, Corruption, Siyasah Syar’iyyah.